Infecções parasitárias na gravidez: prevalência e auto medicação com plantas medicinais na região de Araraquara -São Paulo - Brasil - Martinez, Isabel [UNESP]; Moreira, Raquel Regina Duarte [UNESP]; Cavaleiro, Carlos; Salgueiro, Lígia; Sousa, Maria do Céu; Quilez, Ana Maria; Rosa, João Aristeu da [UNESP]; Miné, Júlio César (My University, 2014)
Pregnant women are individuals own characteristics, metabolic, endocrinological and immunological transient patterns and require special care. To estimate the prevalence of intestinal parasites in pregnant women and use of medicinal plants for self-medication, it is extremely important, because they can lead to miscarriage, fetal death or evil training. The present study aims to conduct parasitological stool examinations in 5.300 pregnant women and interview about the use of medicinal plants. 1.165 women had positive parasitological results, with a predominance of Entamoeba coli. The most cited medicinal plant was “hortelã” (Mentha sp.). To reduce health risks unknown to pregnant woman and her fetus, prophylactic measures against parasites and rational use of medicinal plants in pregnancy, are urgent.

Mulheres grávidas são indivíduos com características próprias, padrões metabólicos, endocrinológicos e imunológicos transitórios e requerem cuidados especiais. Estimar a prevalência de parasitas intestinais em mulheres grávidas e uso de plantas medicinais por automedicação, é de extrema importância, pois podem levar ao aborto, morte ou malformação fetal. O presente trabalho teve como objetivos a realização de exames parasitógicos de fezes em 5.300 mulheres grávidas e entrevista sobre o uso de plantas medicinais. 1.165 mulheres apresentaram resultados parasitológicos positivos, com predominância de Entamoeba coli. A planta mais citada, foi hortelã (Mentha sp.). Para diminuir riscos de saúde desconhecidos para gestante e seu feto, medidas profiláticas contra parasitoses e uso racional de plantas medicinais na gravidez, são urgentes.
Parasitic infections in pregnancy: prevalence and self-medication with medicinal plants in Araraquara region - São Paulo state - Brazil
Keywords: Parasites; Pregnant women; Medicinal plants; Parasitas; Mulheres grávidas; Plantas medicinais